Inovasi Media Pembelajaran Scrapbook Aksawa untuk Belajar Aksara Jawa Siswa Sekolah Dasar - Masjid, Akbar Al; Monika Asti Widya, Astuti; Trisharsiswi, Trisharsiwi; Arya Dani, Setyawan (Kawruh: Journal of Language Education, Literature and Local Culture, 2024)
Javanese language is a compulsory local content in schools from primary to secondary level in Central Java, East Java and Yogyakarta. However, Javanese language lessons, especially Javanese script material for some children, are considered difficult. Based on the results of a survey conducted in several elementary schools in Central Java and Yogyakarta, it is known that almost 90% of students have difficulty reading and writing using Javanese characters. Based on these problems, this research is intended to provide an alternative solution through the development of learning media in the form of Aksawa Scrapbook so that students are more motivated to learn Javanese script. This study uses a research and development (R&D) design with the ADDIE model which consists of analysis, design, development, Implementation, and Evaluation stages. The subjects in this study are students and teachers of elementary schools in Central Java and Yogyakarta. The media feasibility assessment was validated by material experts and media expert validators, as well as classroom teacher practitioners as well as Javanese language teachers. The data collection technique uses observation, interviews and questionnaires. Data analysis techniques use qualitative and quantitative data analysis. The results of this research resulted in a product, namely in the form of Aksawa Scrapbook media. Based on the assessment of experts, practitioners and student responses, the Aksawa Scrapbook media can be declared very feasible to be used for Javanese script learning media in elementary school with an average score of 92.41 with very good criteria. The conclusion of this study is that the script scrapbook media is declared feasible and effective to be used to help students learn Javanese reading and writing skills.